Circulating proliferative factors versus portal inflow redistribution: mechanistic insights of ALPPS-derived rapid liver regeneration - Zhang, Shiran; Ma, Yu; Chen, Xue; Wu, Shuai; Chen, Geng (Frontiers in Oncology, 2025)
BackgroundAssociating liver partition and portal vein ligation for staged hepatectomy (ALPPS) can induce accelerated regeneration of future liver remnant (FLR) and effectively reduce the occurrence of liver failure due to insufficient FLR after hepatectomy, thereby increasing the probability of radical resection for previously inoperable patients with liver cancer. However, the exact mechanism by which ALPPS accelerates liver regeneration remains elusive.MethodsA review of the literature was performed utilizing MEDLINE/PubMed and Web of Science databases in March of 2024. The key words “liver regeneration/hypertrophy”, “portal vein ligation/embolization”, “two-stage hepatectomy”, “liver partition/split” and “future liver remnant” in combination with “mechanisms”, “hemodynamics”, “cytokines”, “growth factors” or “collaterals” were searched in the title and/or abstract. The references of relevant articles were reviewed to identify additional eligible publications.ResultsPreviously, a widely accepted view is that the primary role of liver splitting in ALPPS stage 1 is to accelerate liver regeneration by promoting proliferative factor release, but increasing evidence in recent years reveal that not the circulating factors, but the portal hemodynamic alternations caused by liver parenchyma transection play a pivotal role in ALPPS-associated rapid liver hypertrophy.ConclusionParenchyma transection-induced portal hemodynamic alternations are the main triggers or driving forces of accelerated liver regeneration following ALPPS. The release of circulating proliferative factors seems to be a secondary response to liver splitting and plays an auxiliary role in this process.